Fetal Bovine Serum Meningkatkan Maturasi Inti Oosit Kelinci Setelah Dimaturasi Secara In Vitro - Kurniani Karja, Ni Wayan; Plumeria Aqshani, Winny; Pratiwi Kusumawati, Yesi; Gilang Pravitasari, Veronika; Gustari, Sri (Jurnal Veteriner; Vol 11 No 3 (2010))
This study was conducted to examine the meiotic competence or nuclear maturation of rabbit oocytesmatured in vitro. Oocytes were recovered by mincing the ovaries in modified phosphate buffer saline (m-PBS). Selected cumulus-oocyte complexes (COCs) with compact cumulus cell mass and a dark, homogenousooplasm were cultured in maturation medium at 38°C in a humidified atmosphere of 5% CO2 in air, andthen stained for nuclear maturation. Three experiments were carried out. In Experiment 1, COCs werecultured in maturation medium for 18-20, 22-24, and 28-30 h. The proportion of oocytes at metaphase II(MII) was similar (P>0.05) at 18-20 (69.2%), 22-24 (66.4%), and 28-30 (71.1) h of culture. In Experiment 2,COCs were cultured in either maturation medium containing 0.04% bovine serum albumine (BSA) or 5%fetal bovine serum (FBS) for 24 h. The proprotion of oocytes that reached MII were higher (P<0.05) in FBSgroup (79.2%) than those of oocytes in BSA group (64%). In Experiment 3, based on the presence or absenceof follicles and corpora lutea, the ovarian pairs were classified into follicular or luteal stages. There was nodifference (P>0.05) among oocytes collected from ovaries in follicular (79.7%) and luteal stages (78.7%) inthe ability to achieve nuclear maturation. These results indicated that nuclear maturation of rabbitoocytes in vitro was completed at 18-20 h of maturation culture and was not affected by ovary’s reproductivestage. The presence of FBS in the maturation medium enhanced the ability of rabbit oocytes to achievenuclear maturation.
Keywords: in vitro maturation, rabbit oocytes, bovine serum albumin, fetal bovine serum.